Analisis Kinerja Koperasi Melalui Pemeringkatan Koperasi Berdasarkan Permenkop No. 21/Per/M.KUKM/IX/2015 - Srikalimah Srikalimah; Endah Kurniawati (Owner : Riset dan Jurnal Akuntansi, 2021)
The rating is one of the performance assessments of cooperatives. To find out the ranking of the Multipurpose Joint Venture Cooperative in 2020 is the purpose of this study. The assessment is based on PERMENKOP and SMEs of the Republic of Indonesia Number 21/Per/M.KUKM/IX/2015 concerning Rating of Cooperatives. This research is evaluation research. The types of data used in this study are qualitative and quantitative data, the data sources in this study are primary and secondary. The subjects of this research are the administrators, supervisors, members of KSU Statuegilan. The object of this research is the ranking result of KSU Statuegilan. Collecting data using interview techniques, documentation and questionnaires. The assessment of KSU Sculpture uses ranking as an Evaluation Model. This study shows the results that: (I) In terms of the institutional aspect of the cooperative obtained a score of 720, (II) In terms of the business aspect, the cooperative obtained a score of 112.5 (III) In terms of the financial aspect of the cooperative obtained a score of 197.5, (IV) In terms of Aspects of the benefits of cooperatives to the community get a score of 11. From the accumulated results, a performance assessment score is obtained in terms of the five aspects that have been carried out, KSU Statuegilan obtained a score of 1,076. The score is in the range of scores of 1,000 to 1,200 so that KSU Statuegilan is included as a cooperative with "Berkualitas" qualifications with AAB predicate.